D'une carte inexistante à un empire colonial. La cosmographie de la Renaissance sous la Monarchie espagnole à partir du Padrón Real - Antonio Sánchez (L'Atelier du CRH)
The Spanish Renaissance cosmography developed, throughout the sixteenth century, powerful ‘cognitive devices’ that allow us to explain the scientific narrative of the expansion in a new light. These devices come from the imperial intentions to acquire new knowledge from new worlds. The information was surprising and new and it was thus necessary to issue new structures of organization. To this end, instruments for collecting and management information were developed, which today represent an inexhaustible source of reflection for historians of science. From an epistemological point of view, the Padrón Real (Royal Pattern Chart) and the Relaciones Geográficas de Indias are among the most notable examples. In this paper we analyze the Padrón Real of the Casa de la Contratación in Seville – a map model from which they were made the charts of the Carrera de Indias (maritime and commercial travel between Spain and America) – in an attempt to demonstrate the role played by mapping in the construction of one of the first global empires of modern Europe. From a cartographic analysis of a series of maps, we argue that the Spanish Monarchy attempted to build during the xvith century an impossible map that would establish the visibility of its large overseas empire